Case Study Methodology: Comprehensive Approaches and Examples - M. SAKTHIVEL (AG Volumes, 2024)
The methodology of case studies is the primary focus of this review paper, which examines the various categories of case studies that are employed in research. It examines a variety of case study methodologies, with a focus on both qualitative and quantitative methods. The paper also discusses the essential components of creating effective case studies, emphasising the most effective methods for planning and executing them. The review demonstrates the practical applications and advantages of case studies in offering a comprehensive understanding of intricate issues through a series of examples. This analysis emphasises the importance of case studies as a reliable research instrument in a variety of fields.